Malocclusion traits and speech disorders - Shahbaa AbduGhafoor Mohammed; Jinan Eliewy Saloom; Dina Hamid Obaid; Akram Faisal Alhuwaizi (Medical Journal of Babylon, 2023)
Speech is the ability of communication or expression of thoughts among people in spoken words. Human communication via speech is essential since any impairment in this process may have serious social and occupational consequences. Malocclusion is a possible cause of speech impairment in addition to many other etiological factors like hearing loss, neurological disorders, physical disorders, and drug abuse. This article throws light upon the association between speech disorders and malocclusion.